Analysis of Assalam Family Product Elements in the Implementation of Tabarru' Fund Management: A Case Study on PT. AJS Bumiputera, Medan Branch - Ritonga, Ainun Jakia; Indra, Ahmad Perdana; Harianto, Budi (Borong Newinera Publisher, 2024)
Insurance is a form of financial protection that provides a guarantee of payment or benefit in the face of certain risks or losses. If the unexpected risk befalls one of the participants, the loss will be borne together. The purpose of this study is to analyze and describe the elements of Assalam Family products in the context of the implementation of tabarru' fund management at PT. Bumiputera Sharia Life Insurance Medan Branch. This study uses a type of field research, with qualitative research methods, exploring data through interviews, observations, and document analysis. The results of the research obtained are that the Assalam Family Product Element uses the tabarru' contract as the basis for its implementation. The process involves two procedures, namely requesting an Assalam Family sharia life insurance policy and submitting a claim. Tabarru' funds are managed by separating participants' contributions into two separate accounts, participant savings accounts (saving system) and tabarru' accounts (non-saving system). The investment proceeds are divided 70% for participants and 30% for the company, with a risk management commitment of 50% of the contribution. The allocation of funds is invested in sharia stocks and bonds according to sharia principles. If the tabarru' funds run out, the qardh funds are used to overcome the inadequacy, which is taken from the central Bumiputera which is realized to the branches that lack funds to pay compensation or claims submitted by participants.